Application of Multidisciplinary Systems‐of‐Systems Optimization to an Aircraft Design Problem. Issue 3 (29th August 2016) - Subramanian, Shreyas Vathul; DeLaurentis, Daniel A.
ABSTRACT: A generic mathematical formulation for Systems‐of‐Systems (SoS) optimization problems is presented. SoS optimization problems resemble the structure of a tree of Multidisciplinary Design Optimization (MDO) problems with additional unique features. The framework for solving such problems involves features from evolutionary computing, platform‐based design, and evolving design spaces. One important aspect of SoS Engineering, often overlooked, is the role it plays in improving the design of individual systems. In this vein, this work has sought to exemplify such a synergistic approach for aircraft design. A large‐scale SoS optimization problem for designing noise‐optimal aircraft and improved procedures for the approach phase is studied. Modules involving Computational Fluid Dynamics (CFD), noise modeling, multifidelity analysis, topology optimization, and autotuned control systems are used to obtain optimal solutions.